Identifying Gaps in Academic Writing of ESL students - Giridharan, Beena; Robson, A. (Enhancing Learning: Teaching and Learning Conference 2011 , Curtin University Sarawak, 2011)
There is growing evidence that the lack of competence of university ESL students in academic writing affects their overall academic performance. Olivas and Li (2006) connected low second-language proficiency levels in English to poor academic performance of international students studying at both university and college levels in the United States. Although, many ESL students at university have a general understanding of grammar rules, not many are able to write academically at levels expected of them. This is further exacerbated by a lack of awareness of students’ own ability in academic writing. The paper reports on a case study conducted to identify critical gaps in academic writing standards among ESL students in a foundation studies programme. The study employed a pragmatic case study approach, drawing on qualitative methods as deemed appropriate. In this project, four essential criteria for developing good academic writing skills were investigated; attitudes towards academic writing tasks, planning, writing paragraphs and essays, and evaluating one’s own writing. The study examined the challenges faced by students (n=206) in academic writing and identified common grammatical, structural and syntactic errors made in writing tasks. Data from the study show that most students enjoyed writing tasks and drafting essays and working with peers to brainstorm ideas and opinions for their drafts. A majority of respondents agreed that they were well aware of referencing systems and the need to substantiate their ideas with supportive evidence. However many respondents were unable to evaluate their own work and admitted that often their evaluation did not match that of their instructors. The project aims to propose interventions and techniques to support student academic writing practices in the foundation year.